MENINGKATKAN HASIL BELAJAR PJOK TEKNIK DASAR MENGGIRING BOLA MELALUI PENDEKATAN LAPANGAN - abidin, zainal (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
Learning in class IV on PJOK subject matter, Basic Engineering Material, Herding Ball in Soccer Games, mastery of the material is still very low. Of the 20 number of students only 7 students (35%) who achieved the Minimum Completion Criteria (KKM) were set at 6.5 with an average value of 61.5. To overcome the above problems, the steps that need to be implemented are using the approach to field outside the school. In application, the researcher tried on the subject of PJOK about the concept of "Basic Technique of Dribbling Ball". The subjects in this study were 20 students consisting of 13 men and 7 women. To achieve the results in accordance with what the researcher expects, the researchers implement them with II  cycles. Each cycle is 2  meetings for 3 months. In the first  cycle the average score of students was 68.3 and learning completeness reached 70%, whereas in the second cycle the average score of students was 77 and learning completeness reached 85%. The conclusion of this study is to use the field approach outside the school in the PJOK lesson on material Natural Resources and their use for economic activities can improve learning skills